Cataract-Causing S93R Mutant Destabilized Structural Conformation of βB1 Crystallin Linking With Aggregates Formation and Cellular Viability - Ren, Ling; Hu, Lidan; Zhang, Ying; Liu, Jian; Xu, Wanyue; Wu, Wei; Xu, Jingjie; Chen, Xiangjun; Yao, Ke; Yu, Yibo (Frontiers in Molecular Biosciences, 2022)
Cataract, opacity of the eye lens, is the leading cause of visual impairment worldwide. The crucial pathogenic factors that cause cataract are protein misfolding and crystallin aggregation. βB1-crystallin, which is the most abundant and water-soluble protein in mammalian lens, is essential for lens transparency. A previous study identified a missense mutation βB1-S93R that was associated with congenital cataract. However, the exact pathogenic mechanism causing cataract remains unclear. The 93rd serine residue, which is located at the first Greek-key motif of βB1-crystallin, is highly conserved. On the contrary, hydrogen bonds and protein structural conformation are severely destructed by S93R mutation, which is evaluated via Molecular Dynamic Simulation. The βB1-S93R was also found to be prone to aggregation in both human cell lines and Escherichia coli cells. Therefore, we isolated the partially folded βB1-S93R mutation that was renatured through inclusion bodies. The βB1-S93R mutation exposed more hydrophobic residues, and the looser structural mutation was prone to aggregation. Furthermore, the S93R mutation reduced the structural stability of βB1-crystallin when incubated at physiological temperature and made it more sensitive to environmental stress, such as UV irradiation or oxidative stress. We also constructed a βB1-S93R cellular model and discovered that βB1-S93R was more sensitive to environmental stress, causing not only aggregate formation but also cellular apoptosis and impaired cellular viability. All of the results indicated that lower solubility and structural stability, sensitivity to environmental stress, vulnerability to aggregation, and impaired cellular viability of βB1-S93R may be involved in cataract development.